Mekanisme Neurobiologis dalam Perkembangan Empati dan Perilaku Prososial pada Anak-Anak - Marfita Hikmatul Aini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to explore the neurobiological mechanisms underlying the development of empathy and prosocial behavior in children. The study will use a multidisciplinary approach that combines neuroimaging, neurochemical analysis, and behavioral measurements to understand how children's brains develop in social and emotional contexts. It is hoped that this research will provide in-depth insight into the neurobiological factors that influence children's ability to empathize and act prosocially.